Phân lập các hoạt chất từ rau chua Hibiscus sabdariffa có tác dụng ức chế enzym chuyển hóa Angiotensin I - Linh, Phạm Thùy; Châm, Bá Thị; Thu Hà, Nguyễn Thị; Trà, Nguyễn Thanh; Tú Anh, Lê Thị; Minh Nguyệt, Nguyễn Thị; Tiên, Đoàn Duy; Anh, Ngô Quốc; Tuyến, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
Seven compounds, including methyl 5-O-caffeoylquinate; trimethyl 2-hydroxicitrate; methyl 4-O-caffeoylquinate; caffeic acid; methyl 3-O-caffeoylquinate; methyl 5-O-p-coumaroylquinate and chlorogenic acid were isolated from the bioactivity guided calyces extracts of Hibiscus sabdariffa. Their structures were conﬁrmed by 1H- NMR, 13C-NMR, and MS spectral methods and compared with those reported in the literature. Of these, three quinic acid derivatives; chlorogenic acid and caffeic acid were determined to be Angiotensin converting enzyme inhibitors with IC50 values of 413.76; 569.47; 463.71; 373.25 and 253.12 µg/ml, respectively. These 5 compounds also indicated strong antioxidant capacity with IC50 values at the same range with resveratrol. Keywords: Hibiscus sabdariffa, Quinic acid derivative, Angiotesin I converting enzyme inhibitor, caffeic acid, chlorogenic acid, DPPH.